The alphabet thief who stole the vowels - Villarreal, Claudia; Koch, Michael (Zapata, TX : Dreamstar Publications, 2009)
The approachable antagonist, the Alphabet Thief, hatches a plan to entice and capture all the vowels and whisk them away to a land far more enchanted.But what would happen in a world without vowels?
Keywords: Theft -- Juvenile fiction; Vowels -- Juvenile fiction; Vol (Droit) -- Romans, nouvelles, etc. pour la jeunesse; Voyelles -- Romans, nouvelles, etc. pour la jeunesse; Theft; Vowels